PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 2 KAMANG MAGEK - Auliarahmah, Wilda (Departemen Matematika, 2024)
The objectives of mathematics learning have not been achieved by students, the cause of the low ability to solve mathematical problems is that they are not used to answering non-routine questions. The target of the study was to see whether the ability to solve mathematical problems of class VIII students of SMPN 2 Kamang Magek using the PBL model could be improved. The research was in the form of an experiment, namely a quasi-experiment, in the form of Nonequivalent Posttest Only Control Group. The population was all class VIII students of SMPN 2 Kamang Magek in the academic year 2024/2025. The sample was taken using the total sampling technique. The samples taken were the entire population, namely classes VIII.1, and VIII.2. Theiresearchiinstrument was in the form of a final test of mathematical problem-solving ability in the form of a description. The dataiobtained were tested using normality tests, homogeneity of variance, and hypotheses. The results of the mathematical problem-solving ability test using the t-test method obtained P-Value = 0.04 which is smaller than α = 0.05 which means rejecting H0. It was concluded that students who took part in learning using PBL had the best mathematical problem-solving ability of those who took part in learning with the Direct Learning model.Keywords– mathematical problem solving ability, PBL model, direct learning model